Perception Regarding Hazards of Plastics Usage and Effectiveness of Plastic Ban in Rural Tamil Nadu - Raja Danasekaran; Buvnesh Kumar M; T K Raja; A Y Nirupama; U Sharath (Medsci Publications, 2020)
Background: Plastics have become part of our modern lives and the amount of plastics produced in this decade equals the amount produced in the last century. Unless we control the production and usage of these plastics, the consequences will be drastic. The study was planned to find the perception regarding the hazards of plastics and also to assess the effectiveness of the plastic ban imposed in Tamil Nadu state. Methodology: A cross-sectional study was conducted among adult participants in a rural area (Poonjeri village) of Kanchipuram district in Tamil Nadu. Details regarding basic socio-demography, perception regarding plastics and practices related to plastic ban were collected using a pre-tested questionnaire. Results: The study included 122 participants of which 23.8% were illiterates and 59.8% were unskilled workers.  Major usage form of plastics was plastic covers and they were of the opinion that plastics can lead to cancer, diseases, environmental pollution, etc. 95.1% were aware of the plastic ban and there was difference in awareness about the banned items. Many have stopped using the banned plastics, but 35% were still using plastics for food packing, etc. Plastic wastes were dumped (33.62%) or burnt (21.55%), apart from disposal by local bodies. Conclusion: Even though the awareness about the plastic ban is high among the population, the usage of banned materials is still there. Adequate number of alternatives to be made available and awareness to be created about the same.